Effect of tax planning, deferred tax burden, and deferred tax asset on earnings management - Pratana Puspa Midiastuty; Nila Aprila; Danang Adi Putra; Kartika Widya Sari (Proceeding International Conference on Accounting and Finance, 2023)
This study aims to provide empirical evidence of the effect of tax planning, deferred tax expense, and deferred tax assets on earnings management. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange with an observation period of 2015-2020. By using a purposive sampling method, the number of observations used in this study amounted to 185 observations. The dependent variable in this study is earnings management and the independent variables in this research are tax planning, deferred tax expense, and deferred tax assets. The results of the study provide evidence that tax planning and deferred tax expense have a positive and significant effect on earnings management while deferred tax assets do not affect earnings management. This study supports the agency theory which explains the political costs that must be borne by companies so that the greater the political costs that must be borne by companies encourages companies to carry out earnings management through tax planning and is caused by differences in accounting profit and fiscal profit which result in deferred tax burdens.